Respostas
respondido por:
3
a)
10x + 16 = 14x + 8
16 - 8 = 14x - 10x
4x = 8
x = 8 / 4
x = 2
b)
2x - 6 = - 3x + 9
2x + 3x = 9 + 6
5x = 15
x = 15 / 5
x = 3
10x + 16 = 14x + 8
16 - 8 = 14x - 10x
4x = 8
x = 8 / 4
x = 2
b)
2x - 6 = - 3x + 9
2x + 3x = 9 + 6
5x = 15
x = 15 / 5
x = 3
respondido por:
2
Olá! :)
A) 10 x + 16 = 14 x + 8
16 - 8 = 14 x - 10 x
4 x = 8
x = 8 / 4
x = 2
B) 2 x - 6 = - 3 x + 9
2 x + 3 x = 9 + 6
5 x = 15
x = 15 / 5
x = 3
Abraços! (^_^)
A) 10 x + 16 = 14 x + 8
16 - 8 = 14 x - 10 x
4 x = 8
x = 8 / 4
x = 2
B) 2 x - 6 = - 3 x + 9
2 x + 3 x = 9 + 6
5 x = 15
x = 15 / 5
x = 3
Abraços! (^_^)
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás